North American Women in Iceland: Travel, Travel Writing, and Domestic Feminism, 1866-1939 - Melton, Zachary (Scandinavian-Canadian Studies, 2024)
In the late nineteenth and early twentieth centuries, dozens of travel narratives about Iceland appeared in the United States. The majority of these were written by and for men and women of the wealthier, upper class, as those were the only Americans who could afford to make the long journey to Iceland. However, as the costs of steamship travel became more affordable, a more economically diverse collection of American tourists began visiting Iceland. In many cases, middle-class American women would journey to Iceland and then share their experiences by giving lectures and talks in social clubs, writing articles in more female-focused periodicals like Ladies’ Home Companion, or to giving interviews in their hometown newspapers. In this paper, I will explore the “feminine” space of the social club and the role it played in the perception of Iceland among middle class American women. À la fin du XIXe siècle et au début du XXe siècle, des dizaines de récits de voyage sur l’Islande ont été publiés aux États-Unis. Le plus souvent, ces récits étaient écrits par et pour des hommes et des femmes de la classe fortunée, de la bourgeoisie, vu qu’ils étaient les seuls Américains à pouvoir se permettre de faire le long voyage vers l’Islande. Cependant, à mesure que le coût des voyages en bateau à vapeur devenait plus abordable, des touristes américains plus diversifiés sur le plan économique ont commencé à visiter l’Islande. Dans de nombreux cas, des femmes américaines de la classe moyenne se rendaient en Islande et partageaient ensuite leurs expériences en donnant des conférences et des exposés dans des clubs sociaux, en écrivant des articles dans des périodiques visant un lectorat féminin comme le Ladies’ Home Companion, ou en donnant des entrevues dans les journaux de leur ville natale. Dans cet article, j’explorerai l’espace « féminin » du club social et le rôle qu’il a joué dans la perception de l’Islande parmi les femmes américaines de la classe moyenne.